2020
DOI: 10.1042/bcj20200423
|View full text |Cite
|
Sign up to set email alerts
|

An ATP-responsive metabolic cassette comprised of inositol tris/tetrakisphosphate kinase 1 (ITPK1) and inositol pentakisphosphate 2-kinase (IPK1) buffers diphosphosphoinositol phosphate levels

Abstract: Inositol polyphosphates are ubiquitous molecular signals in metazoans, as are their pyrophosphorylated derivatives that bear a so-called ‘high-energy’ phosphoanhydride bond. A structural rationale is provided for the ability of Arabidopsis inositol tris/tetrakisphosphate kinase 1 to discriminate between symmetric and enantiomeric substrates in the production of diverse symmetric and asymmetric myo-inositol phosphate and diphospho-myo-inositol phosphate (inositol pyrophosphate) products. Simple tools are applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(124 citation statements)
references
References 69 publications
10
112
2
Order By: Relevance
“…And CRLs continue to require neddylation/deneddylation cycles to successfully transduce PSR. This again may be linked to InsPs generated by reverse reactions of IPK1-ITPK1 pair under changed adenylate charge as occurring during Pi-starvation 33,40 . Overall, with our data we highlight IPK1-ITPK1 role in CSN regulations that addresses key aspects of its multi-faceted functions in responding to Pi-imbalances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And CRLs continue to require neddylation/deneddylation cycles to successfully transduce PSR. This again may be linked to InsPs generated by reverse reactions of IPK1-ITPK1 pair under changed adenylate charge as occurring during Pi-starvation 33,40 . Overall, with our data we highlight IPK1-ITPK1 role in CSN regulations that addresses key aspects of its multi-faceted functions in responding to Pi-imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…However, in one striking distinction both ipk1-1 or itpk1-2 accumulate increased levels of Ins(3,4,5,6)P 4 which neither the itpk4-1 nor Col-0 subjected to PSR does 32 . Whether the recently reported reversibility of Ins(3,4,5,6)P 4 to InsP 7 synthesis catalyzed by substrate-product related IPK1-ITPK1 pair and strongly influenced by cellular energy status in principle affects CSN functions need to be investigated further 33,40,41 . In all regards, our model (Fig.5e) proposing that decreased CSN5 deneddylase performance and lower CUL1 deneddylation rates due to loss of IPK1 or ITPK1 nevertheless implicates their activities in CSN roles on CRLs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is blind to inositol generated endogenously from d -glucose-6-phosphate by inositol-3-phosphate synthase 1 (ISYNA1). Therefore, post-column derivatization UV-detection approaches have been developed to avoid radiolabeling 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that inositol tetrakisphosphate 1-kinase 1 (ITPK1), which is present in Asgard archaea, social amoeba, plants, and animals, sequentially phosphorylates Ins(3)P ultimately leading to InsP 6 and PP-InsPs 4 , 12 , 14 . Different InsP pools generated from exogenously acquired or endogenously synthesized inositol can potentially be monitored using chromatography coupled to mass spectrometry (LC-MS) after feeding cells with “heavier” species such as [ 13 C 6 ]-inositol.…”
Section: Introductionmentioning
confidence: 99%
“…A CarboPac PA200 column was eluted with methanesulfonic acid. 43 Substrates and products were detected with a Jasco FP-920 fluorescence detector set at Ex485 nm, 10 nm band pass; Em520 nm, 10 nm band pass, and a gain of 10. Data were exported from ChromNav v1.0 software of the Jasco HPLC machine as ASCII files and redrawn with GraphPad Prism v6.0.…”
Section: Methodsmentioning
confidence: 99%